2020
DOI: 10.1007/s42399-020-00433-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Tigecycline as a Last Resort Therapy in a Patient with Difficult-to-Treat Healthcare-Associated Acinetobacter baumannii Ventriculitis: a Case Report

Abstract: Healthcare-associated ventriculitis and meningitis is a common complication in patients who suffer from head trauma or have undergone a neurosurgery. Healthcare-associated ventriculitis and meningitis is associated with significant morbidity and mortality. Complications of healthcare-associated ventriculitis and meningitis include persistent vegetative state, moderate and severe disability, and death. Acinetobacter baumannii is the causative pathogen in 3.6–11.2% of cases of healthcare-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…IVT tigecycline seemed to be a safe treatment option. In recent years, some studies reported successful application of IVT/ITH tigecycline in patients 36 , 42–47 ( Table 3 ). IVT/ITH tigecycline was administered at doses of 3 to 20 mg per day, and one patient developed liver injury and another developed spinal arachnoiditis, which resolved after discontinuation of the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…IVT tigecycline seemed to be a safe treatment option. In recent years, some studies reported successful application of IVT/ITH tigecycline in patients 36 , 42–47 ( Table 3 ). IVT/ITH tigecycline was administered at doses of 3 to 20 mg per day, and one patient developed liver injury and another developed spinal arachnoiditis, which resolved after discontinuation of the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports described the combination regimens of tigecycline to treat A. baumannii infections, such as bacteremia, VAP, soft tissue, and skin infections [ 126 , 167 ]. A poor correlation has been reported through studies between microbiological and clinical outcomes, mainly among patients under treatment for respiratory tract infections [ 120 , 168 , 169 ]. A low rate (48%) of microbiological eradication with tigecycline treatment has been noticed in A. baumannii hospital-acquired pneumonia (HAP) in some patients, probably due to the lack of adequate tigecycline concentration [ 170 ].…”
Section: Antimicrobial Therapymentioning
confidence: 99%
“…Some antibiotics, such as aminoglycosides, cannot be used intravenously for ventriculitis due to very limited CSF penetration. However, they have been successfully used via the intraventricular route, as demonstrated in small case series and case reports [84,85]. Apart from higher CSF levels, intraventricular administration of vancomycin for Staphylococcal ventriculitis results in a faster reduction in CSF pleocytosis and CSF sterilization [86].…”
Section: Antibioticsmentioning
confidence: 99%